Highways оf the chechen republic under the influence of rockslides аnd screes processes - V. V. Razumov; N. D. Bogdanova; N. V. Razumova; A. A. Likhovid; V. A. Shalnev (Наука. Инновации. Технологии)
The results of systematization and analysis of various sources containing information on the activity and danger of rockslides-screes processes on the roads of the Chechen Republic in 2008-2022 are considered. The greatest rockslides and talus activation (with material damage) on the roads of the republic was observed in 2016-2017. The maximum number of activation cases was in spring-summer period and was mainly due to heavy precipitation. The conditions, causes, activity and danger of rockslides and screes manifestations on the roads of the republic are characterized. During the studied period, about 70 cases (with material damage) were recorded on highways passing through the territory of the Vedensky, Itum-Kalinsky and Shatoy administrative districts of the republic. Information is given on the activity and extent of rockslides-screes deformations and roadbed failures in these areas during the studied period. The greatest rockslides and screes processes activation were observed on the roads of the Shatoy district (more than 40 cases). It was noted that the volume of rockslides and screes masses on the roads of the republic mainly varied from 100 m3 to 17.5 thousand m3. The largest collapse process (30.0 thousand m3) was recorded on October 14, 2008 on the Grozny-Shatoy highway in the Shatoy district. Sections of roads where rockslides and screes were periodically observed in different years have been identified. The length of the sections of the republican highways affected by rockslides-screes processes amounted to 1,452 km, of which: paved roads — 0.546 km, unpaved roads — 0.906 km. The maximum length of sections of the republican highways affected by rockslides-screes processes was noted in 2016 and 2017. The analysis of the socioeconomic consequences of the rockslides-screes processes that have occurred allows us to conclude that their degree of danger to the automobile network of the republic is quite low.